- #1

- 54

- 0

## Main Question or Discussion Point

Hello.

I'm just trying to understanding something here. I was taught integration by parts by my professor in what looks to be like an untraditional way.

From my understanding, the theorem states:

∫udv = uv - ∫vdu

We were given an example in class of:

∫e

=∫e

=-e

I don't understand how this is the same thing as if I were to use, e

∫e

=e

Any help understanding this professors method would be great, thanks!

I'm just trying to understanding something here. I was taught integration by parts by my professor in what looks to be like an untraditional way.

From my understanding, the theorem states:

∫udv = uv - ∫vdu

We were given an example in class of:

∫e

^{x}sin(x)dx=∫e

^{x}∫sin(x)dx - ∫[(e^{x})'∫sin(x)dx]dx=-e

^{x}cos(x) + ∫e^{x}cos(x)dxI don't understand how this is the same thing as if I were to use, e

^{x}as u and sin(x) as v, since the outcome would then be:∫e

^{x}sin(x)dx=e

^{x}sin(x)dx - ∫e^{x}sin(x)dxAny help understanding this professors method would be great, thanks!